Sun and sea tourism : fantasy and finance (of the all-inclusive industry) - Ambrosie, Linda M., 1958- (Cambridge Scholars Publishing, 2015)
Cruise ship passengers and all-inclusive hotel-guests are increasing exponentially as these floating and fixed properties proliferate in size and number. This is especially true for developing economies that consider sun, sand and sea tourism as a form of growth. Tightly integrated, multi-billion dollar global enterprises mix with weak local institutions populated by local officials, some corrupt, vying for more investment to create a toxic cocktail with diminished social benefits as the hangover. Within view of the shoreline and the towering monoliths of hotels and ships, post-secondary educa.